Propuesta experimental para la evaluación del comportamiento y diseño de muros delgados de concreto reforzado DMO en sistemas industrializados (2021)
Framed within the research project EXPERIMENTAL BEHAVIOR OF REINFORCED CONCRETE WALLS WITH MODERATE ENERGY DISSIPATION CAPACITY (DMO) of the CIMOC group of the Universidad de los Andes, this document presents an analysis of the types of common walls in industrialized buildings is presented, an experimental proposal that allows studying the seismic behavior of these walls including the complete design of the assembly for these tests, results of non-linear models simulating the proposed tests and a preliminary analysis of the sensitivity of the coefficient R in the cost of the structure of industrialized buildings.